Simultaneous infection with enterobacteriaceae and pseudomonas aeruginosa harboring multiple carbapenemases in a returning traveler colonized with candida auris (2020)
We report our clinical experience treating a critically ill patient with polymicrobial infections due to multidrug-resistant Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa in a 56-year-old woman who received health care in India and was also colonized by Candida auris. A precision medicine approach using whole-genome sequencing revealed a multiplicity of mobile elements associated with NDM-1, NDM-5, and OXA-181 and, supplemented with susceptibility testing, guided the selection of rational antimicrobial therapy.